Vaccines for preventing enterotoxigenic Escherichia coli infections in farm animals - Moon, Harley W. (Vaccine, 1993)
Fimbrial vaccines are routinely given parenterally to pregnant cattle, sheep and swine to protect suckling newborn calves, lambs and pigs against enterotoxigenic Escherichia coli (ETEC) infections. Such vaccines are practical and effective because (1) most fatal ETEC infections in farm animals occur in the early neonatal period when the antibody titres in colostrum and milk are highest; (2) more than 90% of the ETEC in farm animals belong to a small family of fimbrial antigen types: (3) fimbriae consist of good protein antigens on the bacterial surface where they are readily accessible to antibody; (4) fimbriae are required for a critical step (adhesion-colonization) early in the pathogenesis of the disease. ETEC infections continue to be a significant clinical problem in farm animals in spite of extensive use of fimbriae-based vaccines. Definitive data on the efficacy of the commercial vaccines in field use are not available. The prevailing perception among animal health professionals is that the vaccines are effective, that the problem occurs chiefly among non-vaccinated animals, and that in some herds vaccination moves peak prevalence of disease from the first to the second or third week after birth, when mortality is lower. It has been suggested that extensive use of vaccines will rapidly select for the emergence of novel or previously low prevalence fimbrial antigen types. There is no evidence that this has happened after a decade of routine vaccine use in the United States. However, there is no active direct surveillance for such emergence. In contrast to the rational development of vaccines to provide passive lacteal protection against ETEC in suckling neonates, comparatively little progress has been made in providing the knowledge required for development of vaccines to protect against postweaning ETEC infections in swine.